DINAMIKA PROSES PENERIMAAN PADA IBU YANG MEMILIKI ANAK PEREMPUAN DENGAN ORIENTASI HOMOSEKSUAL - Fika Ayudhia; Elmira N. Sumintardja (MANASA, 2016)
In the society, lesbians tend to reluctant in expressing their sexual orientation. It makes them difficult to gain social support. Having support from the closest people, especially the family, is important. Mothers and daughters have the closest relationship in the family. The deep and personal relationship between mother and daughter may result in such unique difficulties for the mother when she finds out that her daughter is a homosexual. The purpose of this research is to describe the acceptance process of a mother who is facing a daughter with homosexual orientation. The researcher will also discuss other factors that weigh in the acceptance process. This research applies a qualitative approach with two participants, who are mothers with lesbian biological daughters and have already found out about their daughter’s sexual orientation. This research finds out that each participant experienced different dynamics of acceptance process towards her daughter sexual orientation. Generally, a mother begins her acceptance process with the denial phase. The next phases could differ, and several phases could be experienced at the same time. Factors that being consideration in the acceptance process depends on the life condition, values they believe in, and also mother’s personality. Aside from the acceptance of the sexual orientation, this research finds out that a mother tends to keep the good relationship with her daughter, even though she still could not accept the daughter’s sexual orientation.